STEREOTIP TERHADAP PEREMPUAN DALAM NOVEL-NOVEL KARYA ABIDAH EL KHALIEQY: TINJAUAN SASTRA FEMINIS - Puspita, Yenny (LPPM STKIP PGRI Bandar Lampung, 2019)
This study aims to obtain an overview and deep understanding of the role of women in society, especially the stereotypes of women in the novel Perempuan Berkalung Sorban and Geni Jora by Abidah El Khalieqy. This study uses a descriptive qualitative approach. Primary data sources in this study are novels by Abidah El Khalieqy including: Women Berkalung Sorban (2001) and Geni Jora (2004). Data collection techniques are in the form of document searches. In this case, the form of awareness and flow of feminist thought contained in Indonesian literary texts is understood to mean the use of feminism studies. The data analysis procedure used in this study is content analysis.